Procurement auctions with interdependent values and affiliated signals - RM Balanquit; MJM Kimwell (University of the Philippines, School of Economics (UPSE), 2016)
Procurement auctions that assume independent private values (IPV) provide a benchmark for analysis that is readily demonstrated but often unrealistic. Firms who compete for exclusive selling rights normally derive outputs from a highly similar set of inputs which, in turn, allows them to obtain some knowledge on how others would price their goods. In this paper, we incorporate this assumption by showing how affiliated signals and interdependent values can possibly affect the expected quantities sold and selling prices of some endogenous-quantity procurement auction formats. The resulting equilibrium bidding strategies no longer give credence to the typical equivalence result which holds under IPV. In this environment, the second-price auction yields both higher expected prices and lower expected quantities than the first-price auction. This result is consistent with similar studies showing suboptimality of auction mechanisms that allow for winning bids of less-than-the-highest willingness to pay, when values are not fully independent.
Keywords: D44; H57; 330; procurement auctions; affiliated signals; interdependent values; first price vs. second price